2011
DOI: 10.1111/j.1471-0528.2011.02944.x
|View full text |Cite
|
Sign up to set email alerts
|

The risk of preterm birth following treatment for precancerous changes in the cervix: a systematic review and meta-analysis

Abstract: Background Studies investigating the association between treatment for precancerous changes in the cervix and risk of preterm birth have used a variety of comparison groups.Objectives To investigate whether treatment for precancerous changes in the cervix is associated with preterm birth (<37 weeks) and to examine the impact of the type of comparison group on estimates of risk.Search strategy PubMed, Embase and CENTRAL were searched for studies pubished between 1950 and 2009.Selection criteria Eligible studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
148
5
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(168 citation statements)
references
References 48 publications
6
148
5
9
Order By: Relevance
“…Arguably the best available evidence is from three systematic reviews. [2][3][4] Meta-analysis has revealed that excisional methods (LLETZ, cold-knife conisation and laser conisation) were associated with an increased risk of PTL and low birthweight, and that LLETZ was also associated with an increased risk of preterm prelabour rupture of the membranes (PPROM). 2 The large number of linkage studies that followed confirmed the above findings and enabled the assessment of severe outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Arguably the best available evidence is from three systematic reviews. [2][3][4] Meta-analysis has revealed that excisional methods (LLETZ, cold-knife conisation and laser conisation) were associated with an increased risk of PTL and low birthweight, and that LLETZ was also associated with an increased risk of preterm prelabour rupture of the membranes (PPROM). 2 The large number of linkage studies that followed confirmed the above findings and enabled the assessment of severe outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…For pregnant women this approach appears particularly important as only treatment of methylation positive lesions is indicated thereby limiting the risk of preterm delivery resulting from treatment. [118][119][120] .…”
Section: Hsa-mir-124-2 Panel Recently Passed the Later Phases Of Biommentioning
confidence: 99%
“…Furthermore, conization increases the risk for premature birth and late abortions in subsequent pregnancies [15][16][17].…”
Section: Discussionmentioning
confidence: 99%